PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN TERHADAP KINERJA YANG BERDAMPAK PADA PENGEMBANGAN KARIR - Ardiyansah Ardiyansah; Hamdan Hamdan; Adrian Radiansyah (LPPM STIE PERTIBA Pangkalpinang, 2018)
Education is the basic capital to create superior human resources, the performance of teachers in schools has an important role in achieving school goals. This study aims to determine and analyze the influence of leadership, motivation and discipline on performance, as well as analyzing the effect of performance on teacher career development in Toboali 2 Public Middle School, South Bangka Regency. The population in this study were all teachers who worked at SMPN 2 Toboali Bangka Selatan totaling 63 teachers. Based on the results of the analysis concluded that there is the influence of the variables of leadership, motivation, and discipline simultaneously on performance. To improve the work motivation of the teacher, the principal should provide a policy that can motivate the teacher to do the best performance, such as giving appreciation to the accomplished teacher and giving the teacher the widest opportunity to further develop the potential he has. To improve the work discipline of teachers, the principal should improve the guidance and supervision system. The coaching system implemented should vary for example by using the ESQ method. The monitoring system can be improved by using the progress of the information system to monitor the presence of teachers in school and in the classroom.